A Review of the Influence of Vitamin D Deficiency on Muscle Strength and Exercise Performance in Adults - Popow, Weronika; Sadkowska, Paulina; Jania, Katarzyna; Smolińska, Karolina; Kulczycka, Julia; Ciołkosz, Michał; Antczak, Tomasz; Gajda-Bathelt, Monika; Dąbek, Monika; Perlicka, Zuzanna (Quality in Sport, 2025)
Background: Vitamin D plays a crucial role in maintaining musculoskeletal health. A growing body of evidence links vitamin D deficiency with decreased muscle strength and suboptimal exercise performance in adults. Aim: This review aims to synthesize existing research on the effects of vitamin D deficiency on muscle strength and exercise efficiency in adults, identifying the physiological mechanisms involved and discussing the potential clinical implications. Materials and Methods: A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science databases. Studies included original research, systematic reviews, and meta-analyses published in English between 2000 and 2024. Keywords used included "vitamin D," "muscle strength," "exercise performance," "deficiency," and "adults." Results: Most studies support a positive association between adequate vitamin D levels and improved muscle function. Deficiency is linked with reduced type II muscle fiber size, impaired neuromuscular function, and increased inflammation. Supplementation with vitamin D, particularly in individuals with vitamin D deficiency, often results in improved muscle strength and exercise performance, although findings vary by study design and population. Conclusions: Vitamin D deficiency negatively affects muscle strength and exercise capacity in adults. Clinicians should consider monitoring and correcting vitamin D levels, particularly in populations at risk of deficiency. Future research should focus on identifying optimal dosing strategies and the long-term effects of supplementation.